Soil Fungal Communities in the Rhizosphere of Sauvignon Blanc Grapes Subjected to Various Agricultural Management Practices - Nativ Rotbart; Tirza Doniger; Itaii Applebaum; Yosef Steinberger (Land)
The quality and production of viticulture are profoundly shaped by climate and soil, which are vital for enhancing plant growth, maximizing productivity, and facilitating carbon sequestration and phytoremediation. Any degradation in soil quality resulting from production practices—such as salinization and increased acidity—jeopardizes the long-term sustainability of vineyard operations. It is crucial that we prioritize the health of our soil to ensure the future success of our vineyards. This study aims to (1) assess soil fungal diversity under various management practices, (2) compare the relative abundance of sequence reads for different taxa in response to these practices, and (3) analyze shifts in functional guild composition in relation to these management practices. In this investigation, the fungal community composition was analyzed using molecular tools across five locations with distinct land management practices on the same basaltic soil. The findings indicate that vineyard management practices had a substantial impact on fungal diversity, as evidenced by taxonomic alpha diversity metrics, with significant differences observed in comparison to natural pasture and open field conditions. A permutational analysis of variance (PERMANOVA) revealed a highly significant effect of management practices (p < 0.0001) on fungal community structure. The land management practices were found to induce significant (p < 0.05) differences in species diversity between organic sites (organic and conventional) and the natural control site. Furthermore, the composition and functionality of the fungal communities appear to be shaped by the distinct abiotic factors associated with different management strategies that increase the abundance of total soil microorganisms that are affecting the grape yield and its quality.